PLACEMENT TEST AS AN ATTEMPT TO BETTER HELP STUDENTS IN LEARNING A SECOND/FOREIGN LANGUAGE: AN INTERVIEW REPORT - Rusfandi, Rusfandi (Jurnal Ilmiah Bahasa dan Sastra, 2014)
Abstract Assessment is an essential part in teaching and learning process as it usually provides opportunities both for teachers and students to learn. In the context of second or foreign language teaching, assessment is usually conducted to elicit information regarding studentsâ second language ability. This paper reports and analyzes the results of an interview with a university lecturer in Central Sulawesi who was once involved in the construction of a test to place students in different classroom levels. Although it is apparent from the analysis that there are several weaknesses found in the placement test viewed from the six qualities proposed by Bachman and Palmer (1996), there are other essential aspects that need to be learned from the results of the interview by second or foreign language teachers in other teaching contexts.Â Keywords: assessment, placement test, washback